Philosophizing Brecht : critical readings on art, consciousness, social theory and performance - Roessler, Norman; Squiers, Anthony (Consciousness, literature & the arts, 2019)
"This anthology unites scholars from varied backgrounds with the notion that the theories and artistic productions of Bertolt Brecht are key missing links in bridging diverse discourses in social philosophy, theatre, consciousness studies, and aesthetics. It offers readers interdisciplinary perspectives that create unique dialogues between Brecht and important thinkers such as Althusser, Anders, Bakhtin, Benjamin, Godard, Marx, and Plato. While exploring salient topics such as consciousness, courage, ethics, political aesthetics, and representations of race and the body, it penetrates the philosophical Brecht seeing in him the never-ending dialectic--the idea, the theory, the narrative, the character that is never foreclosed. This book is an essential read for all those interested in Brecht as a socio-cultural theorist and for theatre practitioners. Contributors: Kevin S. Amidon, José María Durán, Felix J. Fuch, Philip Glahn, Jim Grilli, Wolfgang Fritz Haug, Norman Roessler, Jeremy Spencer, Anthony Squiers, Peter Zazzali."--